Perspectives of healthcare providers on implementation of long‐acting cabotegravir plus rilpivirine in US healthcare settings from a Hybrid III Implementation‐effectiveness study (CUSTOMIZE). Issue 9 (12th September 2022) - Czarnogorski, Maggie; Garris, Cindy P.; Dalessandro, Marybeth; D'Amico, Ronald; Nwafor, Toyin; Williams, Will; Merrill, Deanna; Wang, YuanYuan; Stassek, Larissa; Wohlfeiler, Michael B.; Sinclair, Gary I.; Mena, Leandro A.; et al.
Abstract: Introduction: CUSTOMIZE evaluated the implementation of long‐acting (LA) cabotegravir + rilpivirine, a novel healthcare provider–administered injectable antiretroviral therapy regimen, in diverse US healthcare settings. Findings from staff‐study participants (SSPs) through 12 months of implementation are reported. Methods: CUSTOMIZE was a phase IIIb, 12‐month, single‐arm, hybrid III implementation‐effectiveness study conducted from July 2019 to October 2020 at eight US clinics of five clinic types: private practice ( n = 2), federally qualified health centre ( n = 2), university ( n = 2), AIDS Healthcare Foundation ( n = 2) and health maintenance organization ( n = 1). Eligible patient participants received monthly cabotegravir + rilpivirine LA injections after a 1‐month oral lead‐in. At baseline, month 4 and month 12, SSPs ( n = 3 each per clinic), including physicians, nurses or injectors, and administrators, completed quantitative surveys and semi‐structured interviews to assess implementation outcomes (acceptability, appropriateness and feasibility of intervention measures), programme sustainability and SSP perceptions of, attitudes towards, and expectations for cabotegravir + rilpivirine LA. Month 12 data collection occurred during the COVID‐19 pandemic. Results: In surveys, SSPs reported high mean total scores for acceptability, appropriateness and feasibility of cabotegravir + rilpivirine LA implementation at baseline (4.43, 4.52 and 4.38 of 5, respectively) and month 12 (4.45, 4.61 and 4.46 of 5, respectively), regardless of clinic type. At month 12, SSPs were positive about the implementation sustainability (mean Program Sustainability Assessment Tool score, 5.83 out of 7). At baseline, SSPs' top concern was patients' ability to maintain monthly appointments (81%); at month 12, 39% had this concern. The proportion of SSPs reporting patient injection pain or soreness as a barrier was consistent at month 12 versus baseline (48% vs. 46%). Most (78%) SSPs reported optimal implementation of cabotegravir + rilpivirine LA in their clinics was achieved in 1–3 months. In interviews, SSP‐reported strategies for successful implementation included teamwork, using a web‐based treatment planner and having a designated person to track appointment scheduling. In month 12 interviews, SSP‐reported structural changes needed for implementation included changing clinic hours and purchasing refrigerators. Conclusions: In CUSTOMIZE, cabotegravir + rilpivirine LA was successfully implemented across a range of US healthcare settings. Barriers were mitigated with minor process adjustments.